What’s the rush? Scanning electron micrographs of Juncus (Juncaceae) seeds - Sievers, C. (Southern African Humanities, 2013)
Scanning electron micrographs of the modern seeds of 12 Juncus (rush) species were made for comparison and possible identification of ancient material from the Middle Stone Age deposits at Sibudu, KwaZulu-Natal. These micrographs are part of a series in this journal aimed at establishing identification literature for southern African archaeobotanical material. No Juncus seeds were identified in the Sibudu archaeobotanical collection.